2014
DOI: 10.4274/tjo.77598
|View full text |Cite
|
Sign up to set email alerts
|

Tek Taraflı Üst Oblik Kas Felcinde Cerrahi Sonuçlarımız

Abstract: Amaç:Tek taraflı üst oblik kas felcinde (ÜOKF) yapılan cerrahi tedavi ve sonuçlarının değerlendirmesi. Gereç ve Yöntem: Kliniğimizde 1999-2009 yılları arasında tek taraflı ÜOKF tanısı alarak opere edilen hastalar retrospektif olarak incelendi. Hastaların demografik özellikleri, cerrahi öncesi bulguları, cerrahi yöntem, komplikasyonlar, kontrol muayeneleri kaydedildi. Bulgular: Çalışma kapsamına alınan 37 hastanın 22'si (%59) erkek, 15'i (%41) kadındı. Hastaların yaşı ortalama 20,6 idi. Kaymanın ilk fark edilme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Suh et al 16 reported that 12 of 13 patients with Brown syndrome had AHP and classified the cases as slight, medium, or severe depending on the amount of AHP and the presence of vertical strabismus in the gaze positions. In their study presenting the surgical outcomes of patients with unilateral superior oblique palsy, Tenlik et al 17 detected AHP in 97.3% of 37 patients. In our study, we observed that different types of AHP can occur in patients with the same diagnosis ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suh et al 16 reported that 12 of 13 patients with Brown syndrome had AHP and classified the cases as slight, medium, or severe depending on the amount of AHP and the presence of vertical strabismus in the gaze positions. In their study presenting the surgical outcomes of patients with unilateral superior oblique palsy, Tenlik et al 17 detected AHP in 97.3% of 37 patients. In our study, we observed that different types of AHP can occur in patients with the same diagnosis ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%